Exploring a Highly D-Galactose Specific L-Arabinose Isomerase From Bifidobacterium adolescentis for D-Tagatose Production - Zhang, Guoyan; An, Yingfeng; Parvez, Amreesh; Zabed, Hossain M.; Yun, Junhua; Qi, Xianghui (Frontiers in Bioengineering and Biotechnology, 2020)
D-galactose-specific L-arabinose isomerase (L-AI) would have much potential for the enzymatic conversion of D-galactose into D-tagatose, while most of the reported L-AIs are L-arabinose specific. This study explored a highly D-galactose-specific L-AI from Bifidobacterium adolescentis (BAAI) for the production of D-tagatose. In the comparative protein-substrate docking for D-galactose and L-arabinose, BAAI showed higher numbers of hydrogen bonds in D-galactose-BAAI bonding site than those found in L-arabinose-BAAI bonding site. The activity of BAAI was 24.47 U/mg, and it showed good stability at temperatures up to 65 ℃ and a pH range 6.0-7.5. The Km, Vmax and Kcat/Km of BAAI were found to be 22.4 mM, 489 U/mg and 9.3 mM-1min-1, respectively for D-galactose, while the respective values for L-arabinose were 40.2 mM, 275.1 U/mg and 8.6 mM-1min-1 . Enzymatic conversion of D-galactose into D-tagatose with BAAI showed 56.7% conversion efficiency at 55 ℃ and pH 6.5 after 10 h.